2020
DOI: 10.3390/antiox9020117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Peptides from Fermented Milk Showing Antioxidant Properties: Mechanism of Action

Abstract: Due to their beneficial properties, fermented foods are considered important constituents of the human diet. They also contain bioactive peptides, health-promoting compounds studied for a wide range of effects. In this work, several antioxidant peptides extracted from fermented milk proteins were investigated. First, enriched peptide fractions were purified and analysed for their antioxidant capacity in vitro and in a cellular model. Subsequently, from the most active fractions, 23 peptides were identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 38 publications
(44 reference statements)
0
44
0
1
Order By: Relevance
“…Four peptides with high antioxidant activity in both chemistry and cell model evaluations have been purified and identified from the pasteurized milk fermented with Lactobacillus acidophilus NCFM ® , Lactobacillus delbrueckii subs. bulgaricus and Streptococcus thermophilus [129]. Fermented meat products can also be used as a source of PAs [130].…”
Section: Microbial Fermentation and Other Food Processingmentioning
confidence: 99%
“…Four peptides with high antioxidant activity in both chemistry and cell model evaluations have been purified and identified from the pasteurized milk fermented with Lactobacillus acidophilus NCFM ® , Lactobacillus delbrueckii subs. bulgaricus and Streptococcus thermophilus [129]. Fermented meat products can also be used as a source of PAs [130].…”
Section: Microbial Fermentation and Other Food Processingmentioning
confidence: 99%
“…The study found that the presence of the hydrophobic amino acids (glycine and proline) and the -SH group of cysteine as an effective hydrogen donor to free radicals in the peptide contributes to its high antioxidative property. In a recent study shown in Table 1, Tonolo et al (2020) identified four novel antioxidative peptides from fermented milk, namely, N-15-M (NTVPAKSCQAQPTTm*), E-11-F (EDELQD-KIHPF), Q-14-R (QGPIVLNPWDQVKR), and A-17-E (APSFSDIPNPIGSENSE), and subjected them to molecular docking analysis to predict the interaction of the Kelch domain of Kelch-like ECH-associated protein 1 (Keap1). Keap1/nuclear factor erythroid 2-related factor 2 (Nrf2) pathway is known to be the main regulatory system for oxidative stress.…”
Section: Antioxidative Activitymentioning
confidence: 99%
“…When an oxidative imbalance takes place, Keap1 and Nrf2 dissociate, followed by the translocation of Nrf2 to the nucleus and bind to antioxidant response element and subsequently activating the overexpression of antioxidant enzymes. Tonolo et al (2020) treated Caco-2 cells with peptides N15-M, Q-14-R, A-17-E, and E-11-F, and found that all cells except the E-11-F-treated cells had increased levels of antioxidant enzymes because the specific amino acid residues in these peptides interact with Keap1 in the binding to the ETGE motif, causing the disruption of Keap1 binding with Nrf2 and subsequent activation of the signaling cascade.…”
Section: Antioxidative Activitymentioning
confidence: 99%
“…Antioxidant peptides have been demonstrated to inhibit excessive ROS (Zhang et al., 2019). There are also many antioxidant peptides found in food, such as SSGPPVPGPMGPMGPR from skipjack tuna bone (Ding, Du, Zhang, Zaman, & Huang, 2019), QGPIVLNPWDQVKR from fermented milk (Tonolo et al., 2020), and VYLPR from egg white protein (Zhang et al., 2019). However, most of them were analyzed single biological activity.…”
Section: Introductionmentioning
confidence: 99%